Tree species diversity and conservation in Ban Tin Tok community forest, Phitsanulok Province, Thailand - SARAYUT RAKARCHA; WORANART THAMMARONG; PRATEEP PANYADEE; JANJIRA MUENREW; ANCHALEE NUAMMEE; THITIMA THARAWOOT; PIYAPORN SAENSOUK; SURAPON SAENSOUK (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Rakarcha S, Thammarong W, Panyadee P, Muenrew J, Nuammee A, Tharawoot T, Saensouk P, Saensouk S. 2026. Tree species diversity and conservation in Ban Tin Tok community forest, Phitsanulok Province, Thailand. Biodiversitas 27 (1): d270146. https://doi.org/10.13057/biodiv/d270146. This study assessed tree species composition, ecological importance, conservation status and local utilization in Ban Tin Tok community forest, Phitsanulok Province, northern Thailand. Data were collected from twenty 10 × 10 m plots (totaling 0.2 ha), recording all trees with DBH ≥5 cm. A total of 28 species from 27 genera and 15 families were identified. The forest was co-dominated by Pentacme siamensis, Pterocarpus macrocarpus and Canarium subulatum, which exhibited the highest importance value indices. The forest exhibited moderate species diversity and moderate-to-high evenness with a Shannon-Wiener index (H′) of 2.40 and a Pielou’s evenness index (J′) of 0.72, reflecting a relatively stable community structure. The conservation assessment revealed that while most recorded species are categorized as Least Concern (LC), a significant proportion requires attention: one species (P. macrocarpus) is classified as Endangered (EN) and three species (Shorea obtusa, Dipterocarpus obtusifolius and Dalbergia cultrata) are Near Threatened (NT); these four species together account for 14.29% of the total 28 species recorded. Ethnobotanical surveys documented 18 species utilized by the local community for purposes, including food, medicine and materials. These findings highlight the high socio-ecological value of this forest. These results suggest that community forests in northern Thailand can serve as vital refuges for threatened species and sustain traditional ecological knowledge. This quantitative baseline supports the necessity for integrated management strategies that balance biodiversity conservation with sustainable local livelihoods.